2020
DOI: 10.1111/anae.15323
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID‐19 on hip fracture management and mortality in a regional trauma centre

Abstract: The effects of COVID-19 on hip fracture management and mortality in a regional trauma centre Older patients and those with comorbidities have worse outcomes from both hip fracture and COVID-19. Furthermore, testing positive for COVID-19 can increase mortality for any surgical procedure [1]. In anticipation of the initial COVID-19 surge, theatre staff were re-allocated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 4 publications
4
11
0
Order By: Relevance
“…Additionally, several studies have shown that a longer hospital stay significantly increases the chance of COVID-19 infection by exposing the patient to the virus [ 8 , 10 , 14 , 15 ]. The nonsignificant reduction in mortality and lethality observed in the present study is aligned with findings from other studies from Spain [ 31 ] and UK [ 32 ], and the shorter hospital stay could be associated with that.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, several studies have shown that a longer hospital stay significantly increases the chance of COVID-19 infection by exposing the patient to the virus [ 8 , 10 , 14 , 15 ]. The nonsignificant reduction in mortality and lethality observed in the present study is aligned with findings from other studies from Spain [ 31 ] and UK [ 32 ], and the shorter hospital stay could be associated with that.…”
Section: Discussionsupporting
confidence: 92%
“…[ 37 ] Our mean TTS was 20.0 hours (SD 14.3). Although fluctuation did occur, the TTS was within 24 hours even in Period B and Period C. Within the global literature, TTS during the pandemic varied with some authors reporting faster, [ 13 ] slower, [ 12 , 33 ] and equivalent times [ 6 , 9 , 10 , 34 , 35 ] to surgical fixation (Table 4 ). In the presented report, our level 1 trauma center preserved capacity to provide timely access to OR for hip fracture patients notwithstanding protocol changes that included the reduction of operating rooms for orthopaedic trauma from 4 ORs to 1.…”
Section: Discussionmentioning
confidence: 99%
“…Craig et al (December, 2020) [13] United Kingdom March 24 to May 23, 2015-2020 700 ↑ (P = .05) ND (P = .71)…”
Section: Hip Fx Volmentioning
confidence: 98%
“…Despite advice from public health organizations worldwide to avoid social contact and remain at home where possible, the number of patients requiring urgent surgery (such as hip fracture surgery) may not have changed. 10 Given the continuing increase in the number of people affected worldwide by SARS-CoV-2 and the serious consequences of having any surgery with a potential infection, any option to mitigate the spread and b Referenced to ''Americas'' (= 0) c Referenced to ''practitioner's category other than staff/faculty/consultant'' (= 0) d Referenced to ''setting other than academic institute/university hospital'' (= 0)…”
Section: Discussionmentioning
confidence: 99%